Systematics and distribution of family Papilionidae (Lepidoptera: Rhopalocera) in South-Western Borneo - Shahirah, Abd Samad (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Systematics knowledge is required for further taxonomic and ecological research of any taxa. Although the Papilionidae of Borneo has been well documented but the knowledge on the Papilionidae of South-Western Borneo is still lacking. Hence, a review of the systematics and distribution of Papilionidae (Lepidoptera; Rhopalocera) is presented. A total of 302 specimens of 28 species were examined and three tribes were identified; Troidini, Leptocircini and Papilionini. There is no representative from tribe Teinopalpini in the collection. Overall diversity and abundance had shown that the tribe Papilionini has the most species distributed in the South-Western Borneo region and most of the ecological habitats were dominated by the tribe Papilionini too. Larval host plant plays the utmost importance in the development of the larval stage of Papilionidae butterflies. They also serve as food source for this family as some of them are foodplant-specific. Systematics accounts were presented as to identify some of the Papilionidae species found in the SouthWestern Borneo based on the UNIMAS Insect Reference Collection. This study highlighted the importance of systematics knowledge in conservation of Papilionidae butterflies and more studies should be done on the systematics, distribution and dispersal of this family as they possessed much importance in ecological research.